Oracle database 12c release 2 multitenant - Els, Anton (Oracle Database certified master) (McGraw-Hill Education, 2017)
"Govern a scalable, extensible, and highly available enterprise database environment using the practical information contained in this Oracle Press guide. Written by a team of Oracle Masters, Oracle Database 12c Release 2 Multitenant shows, step-by-step, how to deploy and manage multitenant configurations across IT frameworks of all types and sizes. Find out how to create databases, work with PDBs and CDBs, administer Oracle Net Services, and automate administrative tasks. Backup and recovery, security, and advanced multitenant options are covered in complete detail. Learn how to: - Build high-performance multitenant Oracle databases - Create single-tenant, multitenant, and application containers - Establish network connections and manage services - Handle security using authentication, authorization, and encryption - Back up and restore your mission-critical data - Work with point-in-time recovery and Oracle Flashback - Move data and replicate and clone databases - Work with Oracle's Resource Manager and Data Guard"--